Relationship between tax avoidance and institutional ownership over business cost of debt - Nguyen Minh Hai; Tran Thi Phuong Trang; Pham Minh Vuong (Cogent Economics & Finance, 2022)
Beginning with classical theories on finance, such as the capital structure theory, the trade-off theory of capital structure, and the pecking order theory, the literature shows a negative correlation between tax avoidance and institutional ownership with respect to the business cost of debt. However, the impact of tax avoidance and institutional ownership on corporate debt policy in Vietnam is an under-researched topic. The aim of the study is to identify the effect of those mentioned factors on business borrowing policy, using data on 207 companies listed on the Ho Chi Minh City Stock Exchange (HOSE) in Vietnam from 2008 to 2016. The study employs model proposed by Lim in 2009 to achieve mentioned research object with Feasible Generalized Least Squares (FGLS) method to overcome for any defection. The study results show no conclusive empirical evidence of a relationship between business's cost of debt and tax avoidance and institutional ownership. This result contrasts with the conclusion in previous studies and can be explained by the characteristics of the funding market in Vietnam where financial organizations often focus on business results and management efficiency in making lending decisions and this characteristic is at no sign of change soon.
Keywords: G23; G32; H26; 330; Cost of debt; institutional ownership; tax avoidance; HOSE; HNX